2002
DOI: 10.1515/jbcpp.2002.13.4.263
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanisms of Post-Rest Adaptation in the Isolated Electrically Driven Left Atria of Rats

Abstract: We studied the role of the resting period (1, 2, 4, 8, 16 min; n = 6-7), external Ca2+ (0.2, 0.4, 0.6 g/l; n + 5-6), stimulation frequency (1, 2, 3 Hz; n = 6), 4-aminopyridine (4-AP, 2 mM; n = 5); theophylline (1 mM; n = 6), ouabain (5 microM; n = 6), and verapamil (1 microM; n = 6) on post-rest adaptation in the isolated left atria of rats driven electrically by a 2x threshold intensity for 2 ms. Resting periods resulted in three-phasic adaptive changes in contractility during the post-rest stimulation before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Initiation of muscle contraction is achieved by mutual participation of several cellular components including elevation of cytoplasmic free Ca +2 concentration mediated by depolarization of the cell membrane and spatial activation of dihydropteridine receptors (DHPRs), calcium-induced Ca +2 release through ryanodine-sensitive Ca +2 receptors (RyRs), IP 3 /Ca +2 release receptors (IP 3 -R) and the activation of membrane enzyme PLC generating IP 3 and DAG, respectively. Experimental results repeatedly suggested that 4-AP inter-acted with depolarization process (4), dihydropteridinesensitive Ca +2 channels (4,9) and sarcoplasmic Ca2+/ ATPase (11). It was rather unexpected to explore that 4-AP induced contracture in the spontaneously beating frog ventricular strips in the absence of Ca 2+ (4), a finding indicating that the source of Ca 2+ should be intracellular in origin, namely sarcoplasmic Ca +2 stores and/or Ca +2 loosely bound to phospholipids at the inner surface of the cell membrane.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Initiation of muscle contraction is achieved by mutual participation of several cellular components including elevation of cytoplasmic free Ca +2 concentration mediated by depolarization of the cell membrane and spatial activation of dihydropteridine receptors (DHPRs), calcium-induced Ca +2 release through ryanodine-sensitive Ca +2 receptors (RyRs), IP 3 /Ca +2 release receptors (IP 3 -R) and the activation of membrane enzyme PLC generating IP 3 and DAG, respectively. Experimental results repeatedly suggested that 4-AP inter-acted with depolarization process (4), dihydropteridinesensitive Ca +2 channels (4,9) and sarcoplasmic Ca2+/ ATPase (11). It was rather unexpected to explore that 4-AP induced contracture in the spontaneously beating frog ventricular strips in the absence of Ca 2+ (4), a finding indicating that the source of Ca 2+ should be intracellular in origin, namely sarcoplasmic Ca +2 stores and/or Ca +2 loosely bound to phospholipids at the inner surface of the cell membrane.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms underlying the interaction of 4-AP with several excitable cell-lines appeared to be rather complex and have not been fully explored. Experimental results steadily suggested that the mechanisms subserving its effects at the cellular and molecular level may involve inhibition of K+-channels (1-4), promotion of transmembrane Ca 2 +-influx (3,4), release of Ca 2+ from SR (6,7), inhibition of Ca 2+ -ATPase (11) or the interaction of 4-AP with intracellular Ca 2+ -depots (3)(4)(5)(6)(7)9). Indeed, induction of contracture by 4-AP in Ca 2+ -free media strongly suggested that it interacted with SR and that the source of Ca 2+ responsible for such a contracture should be of sarcoplasmic Ca 2+ stores (7,9).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations